Cost-Effectiveness of Rapid Diagnostic Tests (RDTS) for Dengue in Pediatric Emergency Settings - Anand Kumar Jha; Md. Ashfaque Ansari; Ravi Shankar Gupta (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Dengue is a flavivirus infection spread by Aedes aegypti and Aedes albopictus mosquitoes and is estimated to infect up to 400 million people worldwide each year. The IgM capture ELISA has become the most accepted technique for the diagnosis of dengue in developing countries like Nepal. For the early detection Rapid Diagnostics Tests (RDT) is the most appropriate method to be used in emergency setting. This study aims to study about the RDTs and analyze its cost effectiveness among pediatric patient of emergency department as it is the most required method for early diagnosis in the warning stage to prevent unnecessary expenditure in hospitalization and extra tests. MATERIAL AND METHODS This study was conducted from the health care system perspective for the cost effectiveness analysis (CEA) to evaluate the potential financial impact on implementing Rapid diagnostic tests (RDT) for the diagnosis of dengue in the pediatric cases of emergency settings. RESULTS The rapid diagnostic tests decreased 66.22% of the cost to the child who attended emergency department with the suspicion of the dengue with Rs. 1520 of savings per patient. Among the total attendees, 86.5% suffered from high grade fever 69% had other warning signs. RDT proved its significance with only 16% of hospitalizations and zero mortality rates in the study period. CONCLUSION This study reported that RDT can be a suitable way for early triage and diagnosis meeting the health care needs and budget of the individual.